2022
DOI: 10.3390/s22176599
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Fault Diagnosis Using Piecewise Aggregate Approximation and Complete Ensemble Empirical Mode Decomposition with Adaptive Noise

Abstract: Complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) effectively separates the fault vibration signals of rolling bearings and improves the diagnosis of rolling bearing faults. However, CEEMDAN has high memory requirements and low computational efficiency. In each iteration of CEEMDAN, fault vibration signals are added with noises, both the vibration signals added with noises and the added noises are decomposed with classical empirical mode decomposition (EMD). This paper proposes a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…If the sampling frequency is 25,600 Hz and the signal duration is 3.75 s. For the extraction of fault characteristics in variable-speed rolling bearings, the information contained in a signal of this duration is not enough. However, longer signals provide more reliable information [ 21 ], especially when the rolling bearing signals are of long duration under variable-speed conditions, direct processing of short signals is not conducive to observing the changes in fault frequencies of rolling bearings over time.…”
Section: Introductionmentioning
confidence: 99%
“…If the sampling frequency is 25,600 Hz and the signal duration is 3.75 s. For the extraction of fault characteristics in variable-speed rolling bearings, the information contained in a signal of this duration is not enough. However, longer signals provide more reliable information [ 21 ], especially when the rolling bearing signals are of long duration under variable-speed conditions, direct processing of short signals is not conducive to observing the changes in fault frequencies of rolling bearings over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, EMD has its limitations as it is sensitive to noise, leading to decomposition results prone to mode aliasing and distortion of the results in the presence of strong noise background. Hu et al [9] applied Piecewise Aggregate Approximation to the improved method of EMD known as complete ensemble EMD (EEMD), thereby enhancing the computational efficiency of the algorithm. Then, a fast and adaptive EMD method was proposed in [10], which can effectively extract the key feature information of fault signals and has strong practicability because of the low calculation cost.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing studies on vibration detection methods in NDT for identifying the conditions of industrial equipment (e.g., applications in bearings) are attracting significant attention, owing to their optimized and controlled strategies. For example, scholars have studied the fault diagnosis methods of bearings based on vibration signals, including wavelet packet analysis [ 9 ], Complete Ensemble Empirical Mode Decomposition with Adaptive Noise (CEEMDAN) [ 10 ], the Teager–Kaiser Energy Operator [ 11 ], support vector machines (SVMs) [ 12 , 13 ], neural networks (NNs) [ 14 , 15 ] and enhanced differential product weighted morphological filtering [ 16 ]. Given this, it was observed that when the HVCB fails, there is also an abnormal vibration signal which can be used to analyze the HVCB’s running state.…”
Section: Introductionmentioning
confidence: 99%